2009
DOI: 10.1001/archgenpsychiatry.2009.158
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of DSM-IV Major Depressive Disorder as a Consequence of Subthreshold Bipolarity

Abstract: Data suggest that MDD is a heterogeneous concept including a large group with subthreshold BPD, which is clinically significant and shares similarities with BPD. Findings might support the need for a broader concept and a more comprehensive screening of bipolarity, which could be substantial for future research and adequate treatment of patients with bipolarity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
205
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(233 citation statements)
references
References 50 publications
(90 reference statements)
21
205
2
2
Order By: Relevance
“…Indeed it may be that this association is less likely than a longitudinal association with psychotic experiences as, whilst it has been found that chronic immune activation occurs in schizophrenia, previous research has suggested that bipolar disorder is an episode-related inflammatory syndrome, with normal cytokine function between affective episodes (Kunz et al 2011;Stertz et al 2013). Hypomanic symptoms in early adulthood are a risk factor for developing bipolar disorder (Zimmermann et al 2009), but are also associated with increased future risk of non-affective Axis I disorders, personality disorders, mental health service use and psychotropic drug prescribing (Päären et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed it may be that this association is less likely than a longitudinal association with psychotic experiences as, whilst it has been found that chronic immune activation occurs in schizophrenia, previous research has suggested that bipolar disorder is an episode-related inflammatory syndrome, with normal cytokine function between affective episodes (Kunz et al 2011;Stertz et al 2013). Hypomanic symptoms in early adulthood are a risk factor for developing bipolar disorder (Zimmermann et al 2009), but are also associated with increased future risk of non-affective Axis I disorders, personality disorders, mental health service use and psychotropic drug prescribing (Päären et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In the National Comorbidity Survey Replication (NCS-R) study, a nationally representative, face-to-face, household survey of the U.S. population conducted between February of 2001 and April of 2003, nearly 40% of study participants with a history of MDD had subthreshold hypomania (defined as the presence of three or more manic symptoms). 2 Previous reports suggested that, compared to pure major depression, major depressive disorder with mixed features is associated with greater illness severity, [8][9][10][11] increased frequency of recurrent depressive episodes, 2,11 increased risk of suicide attempts, 2,7,11-13 a high frequency of substance abuse, 2,7,11 and greater functional impairment. 2,6,11 MDD with mixed features has recently been endorsed as a clinically distinct and valid entity by its inclusion in the Diagnostic and Statistical Manual of Mental Disorders, 5h ed.…”
Section: Introductionmentioning
confidence: 99%
“…14 Lurasidone is an atypical antipsychotic agent with high affinity for D 2 , 5-HT 2A , and 5-HT 7 receptors (K i = 1, 0.5, and 0.495 nM, respectively). 15 In animal models, the antidepressant effect of lurasidone has been shown to be mediated in part by antagonist activity at the 5-HT 7 receptor. [16][17] Lurasidone has demonstrated efficacy in the treatment of major depressive episodes associated with bipolar I disorder (bipolar depression), both as a monotherapy and as an adjunctive therapy with lithium or valproate.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12] In MDD patients without mixed features, the presence of concurrent anxiety has been shown to reduce the likelihood of achieving an adequate antidepressant response. [19][20][21][22][23][24][25][26][27] We report here the results of a post-hoc analysis of a placebo-controlled, 6-week trial of MDD presenting with mixed features and anxiety which found that treatment with lurasidone significantly improved depressive symptoms in a subgroup of patients with moderate-to-severe anxiety at baseline.…”
Section: Lurasidone For Mdd With Mixed Features and Anxiety 241mentioning
confidence: 99%
“…1 The available evidence, largely from clinical study populations, suggests that major depressive disorder (MDD) with mixed features may occur in at least 25% of patients with major depression. [2][3][4][5][6][7][8][9][10][11][12] In patients with a diagnosis of MDD, the estimated lifetime prevalence of an anxiety disorder is greater than 35%. 13,14 The presence of comorbid anxiety in MDD has been found to be associated with greater illness severity, chronicity, and functional impairment.…”
Section: Introductionmentioning
confidence: 99%